Anti-Corrosion Properties of a TCP Pretreatment Conversion Coating on Aluminum Alloy 2024-T3 during Moist SO2 Atmospheric Testing: Effects of Galvanic Coupling. Issue 4 (1st January 2017) - Whitman, Brandon W.; Li, Liangliang; Swain, Greg M.
Abstract : The anti-corrosion properties of a trivalent chromium process (TCP) conversion coating on Cu-rich aluminum alloy 2024-T3 were studied when galvanically coupled to an uncoated Ti-6Al-4V fastener. Coated and uncoated test specimens were exposed to a 14-day moist SO2 exposure (40 ± 3°C, 360 ppm SO2, 336 h). The TCP coating (Bonderite T5900, Henkel) provided corrosion resistance to this alloy in this acidic environment both stand-alone and when galvanically coupled. The results revealed that the stand-alone corrosion protection of the coating is excellent during the exposure. Roughness, pit density, pit depth and pit diameter are all significantly reduced as compared to the uncoated control. The coating also provided excellent resistance against galvanic corrosion. Corrosion damage and corrosion product formation were confined to the region under the contacting fastener head. Regions away from the through-hole were largely free of discoloration and pitting. Electrochemical parameters, Rp and icorr, were good predictors of the trends observed during the SO2 testing. Corrosion of the alloy initiates at sites where the conversion coating and or the native oxide does not cover and passivate the surface. Corrosion leads to the formation of a Alx (OH)y (SO4 )z product layer that undercuts the TCP coating. The corrosion product eventually passivates the surface. By and large, the TCP coating remains intact and passivating after the 14-day exposure.